2014
DOI: 10.1016/j.vph.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative activation of the Ca2+/calmodulin-dependent protein kinase II (CaMKII) regulates vascular smooth muscle migration and apoptosis

Abstract: Activation of the Ca2+/calmodulin-dependent protein kinase II (CaMKII) and reactive oxygen species (ROS) promote neointimal hyperplasia after vascular injury. CaMKII can be directly activated by ROS through oxidation. In this study, we determined whether abolishing the oxidative activation site of CaMKII alters vascular smooth muscle cell (VCMC) proliferation, migration and apoptosis in vitro and neointimal formation in vivo. VSMC isolated from a knock-in mouse with oxidation-resistant CaMKIIδ (CaMKII M2V) dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Oxidation-dependent activation of CaMKII␦ contributes to myocyte apoptosis during myocardial infarction (9), atrial fibrillation (30), and vascular smooth muscle cell migration after vascular injury (31). CaMKII␦ is also activated by O-GlcNAc modification, which contributes to hyperglycemia-induced Ca 2ϩ leaking and arrhythmia (10).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidation-dependent activation of CaMKII␦ contributes to myocyte apoptosis during myocardial infarction (9), atrial fibrillation (30), and vascular smooth muscle cell migration after vascular injury (31). CaMKII␦ is also activated by O-GlcNAc modification, which contributes to hyperglycemia-induced Ca 2ϩ leaking and arrhythmia (10).…”
Section: Discussionmentioning
confidence: 99%
“…Mice expressing an oxidation-resistant CaMKII (M281/282V) were found to be protected from diabetes-attributable mortality after myocardial infarction (55). In the vasculature, CaMKII Met281/282 oxidation occurs in conditions of increased oxidative stress and promotes smooth muscle migration and apoptosis (60, 61). Importantly, CaMKII Met281/282 oxidation has been shown to be involved in regulation of the NF-κB pathway and inflammatory mechanisms associated with cardiac hypertrophy and asthma (26, 62).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injury and inflammation affect the normal function of VSMC and play a major role in atherogenesis (Gambardella and Santulli, 2016). Various inflammatory cytokines, such as Tumor necrosis factor-α (TNF-α), Interferon-γ (IFN-γ), and Interleukin-2 (IL-2) have been associated with dysfunction in EC and VSMC, which are among the key contributors resulting in various vascular diseases, such as atherosclerosis (AS), hypertension, and vascular stenosis (Ho et al, 2010; Lu et al, 2013; Stone et al, 2013; Zhu et al, 2014). Studies have demonstrated that the pathogenesis of AS is closely associated with the dysregulation of VSMC proliferation, migration, and apoptosis (Shen et al, 2014; Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various inflammatory cytokines, such as Tumor necrosis factor-α (TNF-α), Interferon-γ (IFN-γ), and Interleukin-2 (IL-2) have been associated with dysfunction in EC and VSMC, which are among the key contributors resulting in various vascular diseases, such as atherosclerosis (AS), hypertension, and vascular stenosis (Ho et al, 2010; Lu et al, 2013; Stone et al, 2013; Zhu et al, 2014). Studies have demonstrated that the pathogenesis of AS is closely associated with the dysregulation of VSMC proliferation, migration, and apoptosis (Shen et al, 2014; Zhu et al, 2014). EC provide an interface between blood and vessel walls, interact in close proximity with VSMC, and contribute to VSMC proliferation and migration (Nagel et al, 1994; Zitman-Gal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%